FREE SEX ATTITUDE OF YOUNG ADOLESCENTS AND PERSONALITY STRUCTURE OF SIGMUN FREUD - Djibran, Moh. Rizki; Wenny Hulukati; Irvan Usman (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
this study discusses free sex attitude of young adolescent and personality structure of Sigmund Freud. The first part of this paper examines young adolescents’ problem and the second part is about personality structure of Sigmund Freud. Free sex attitude of young adolescents is, nowadays, unresolved social issue which should not considered as simple issue due to its serious impact that may appear. This is an action which breaks certain norms and harm nation young generation. Young adolescent is a growth and development period of human life, in a process of growth from birth to transition period, from childhood to adulthood. In teen phase, improvement of sexual drive is the cause of free sex. Free sex is an attitude which is based on sexual drive to obtain sexual pleasant with opposite sex and it is out of legal marriage status. Personality structure of Sigmund Freud comprises three systems namely: id, ego and superego. These three aspects are psychological structure. Human personality acts or functions intact instead of separated segments. Id is a biological component, while ego is psychological component and superego is social component. Reviews of both personality structure of Sigmund Freud and free sex attitude of young adolescent are: (1) id: sexual drive improves and biological sexual maturity is imbalance with psychological maturity, (2) ego: Kissing, Necking, Petting and Intercourse, (3) superego: bad morality of the young adolescents in responding sexual drive.